Dollar Invoicing, Global Value Chains, and the Business Cycle Dynamics of International Trade - Cook, David (IMF Working Papers; Working Paper ;, 2022)
Recent literature has highlighted that international trade is mostly priced in a few key vehicle currencies and is increasingly dominated by intermediate goods and global value chains (GVCs). Taking these features into account, this paper reexamines the relationship between monetary policy, exchange rates and international trade flows. Using a dynamic stochastic general equilibrium (DSGE) framework, it finds key differences between the response of final goods and GVC trade to both domestic and foreign shocks depending on the origin and ultimate destination of value added and the intermediate shipments involved. For example, the model shows that in response to a dollar appreciation triggered by a US interest rate increase, direct bilateral trade between non-US countries contracts more than global value chain oriented trade which feeds US final demand, and exports to the US decline much more when measured in gross as opposed to value added terms. We use granular data on GVCs at the sector level to document empirical evidence in favor of these key predictions of the model.